Meningkatkan Keterampilan Berpikir Kritis Siswa Menggunakan Model PBL, NHT dan Talking Stick Melalui Media EduNusa Pada Kelas IV Sekolah Dasar: - Puspita Sari; Tika Puspita Widya Rini (STKIP Subang, 2025)
The objective of this study was to enhance students’ critical thinking skills in the IPAS subject through the implementation of the PBL, NHT, and Talking Stick models, along with the use of EduNusa media. This research employed a Classroom Action Research (CAR) method, conducted over four meetings following the steps of planning, action, observation, and reflection. The subjects of the study were 12 fourth-grade students at SD Kristen Banjarmasin during the 2024/2025 academic year. The findings of the study indicate significant improvements across all aspects. Teacher activity increased from a score of 18 to 24. Student activity rose from 58% to 92%. Students’ critical thinking skills also showed substantial growth, increasing from 50% to 92%. Likewise, student learning outcomes improved from 50% to 92%. The results indicate that the implemented instructional strategies had a positive influence on student engagement, critical thinking abilities, and academic achievement. It can be concluded that the integrated use of PBL, NHT, and Talking Stick models, supported by EduNusa media, is effective in enhancing students’ critical thinking skills and learning outcomes in the IPAS subject.